Response of Growth, Yield and Yield Components of two Sunflower Varieties (Helianthus annuus L.) to Nitrogen Fertilization - Hama, Shara Jalal (Sulaimani Journal for Pure and Applied Sciences, 2015)
A field study was conducted at spring 2013 in the experimental farm of the Faculty of Agricultural Science, University of Sulaimany at Bakrajo, to evaluate the response of some growth characters, yield and yield components of two varieties Flame and Sirena and three Nitrogen fertilization on growth and yield sunflower (Helianthus annaus L .).The experiment comprised of two varieties of sunflower (Flame and Sirena) and Nitrogen fertilization levels (0, 100 and 200) Kg (urea) ha-1. Arranged as Split-Plot in Randomized Completely Block Design with three replications. performances in term of plant height, leaves number and stem diameter were evaluated. The important character of yield, yield components and growth were also evaluated. The Nitrogen fertilizer levels were implemented in the main plots and varieties implemented in the sub-plots. The results showed no significant differences between varieties in growth characters with exception of stem diameter, while it was found to be significant on all yield characters with exception of disk diameter, there were no significant differences of nitrogen levels on growth characters with exception of number of leaves plant -1, while it was found to be highly significant on all yield characters. The effect of interaction between varieties and Nitrogen levels were no significant for all growth characters, yield and yield components continue. The highest percentage of oil represented in the variety (Flame) under the treatment of control.
Keywords: Sunflower; Nitrogen fertilization; Growth characters; Yield components and Oil contents